Composition of Growing Media and Concentration of Foliar Fertilizer Affected Yield and Quality of Purple Eggplant (Solanum melongena L.) - Ramdan Hidayat; Melinda Dwi Safitri; Pangesti Nugrahani (Jurnal Ilmu Pertanian Indonesia, 2025)
The study aimed to obtain the best combination of growing media composition and the concentration of foliar fertilizer (Gandasil B) on the yield quality of eggplant. The research was conducted from December 2022 to February 2023 in Nganjuk Regency, using a completely randomized design of two factors. The first factor was composition of the growing media, which comprised of soil:husk charcoal:cow manure with ratios of (1:1:1), (1:1:2), (1:2:1), and (2:1:1), and the second factor was the concentration of foliar fertilizer (0, 2, 4, 6 g/L). The results exhibited that the combination of (1:2:1) medium growing composition and the 2 g/L concentration of foliar fertilizer produced the best fruit diameter with an increase of 22.35% compared to the combination of growing media (1:1:1) and concentration of foliar fertilizer of 2 g/L. The composition of the soil growing medium 1:2:1 gave the best results on fruit length and diameter, average fruit weight, and total fruit weight per plant. A quadratic regression analysis of the concentration of foliar fertilizer and the number of purple eggplant fruits showed that the highest concentration of foliar fertilizer was 5.78 g/L. Keywords: foliar fertilizer, fruit diameter, growing medium, purple eggplant